The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1590/s0034-70942008000300013
|View full text |Cite
|
Sign up to set email alerts
|

Anestesia regional intravenosa primeiro centenário (1908-2008): Início, desenvolvimento e estado atual

Abstract: Intravenous regional block is the anesthetic technique created by A. K. G Bier exactly 100 years ago. In the first half of the 20th Centuty, it evolved little and slowly, but in the last several years, it has seen an accentuated improvement, thanks to countless technical, pathophysiological, pharmacological, pharmacokinetic, and clinical developments, for which Brazilian Anesthesiology has contributed considerably. Since it is celebrating its 100th anniversary in 2008, intravenous regional block deserves to ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 68 publications
0
4
0
1
Order By: Relevance
“…With Bier block, it has been shown that after tourniquet release a significant portion of the local anesthetic remains in the operated limb for a prolonged time. 20 When performing surgery with a tourniquet, there is a 10-to 15-minute time frame between ropivacaine infiltration and restoration of the blood flow. During this period, systemic absorption is absent and postponed until the time of deflation.…”
Section: Discussionmentioning
confidence: 99%
“…With Bier block, it has been shown that after tourniquet release a significant portion of the local anesthetic remains in the operated limb for a prolonged time. 20 When performing surgery with a tourniquet, there is a 10-to 15-minute time frame between ropivacaine infiltration and restoration of the blood flow. During this period, systemic absorption is absent and postponed until the time of deflation.…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous regional anesthesia (IVRA) is used in outpatient hand surgery as an easily applicable and cost-effective technique with clinical advantages and it is an ideal anesthetic method particularly for short lasting procedures [ 1 ]. Although IVRA has a history more than a century old, it has regained importance in the recent years as an effective and safe technique [ 2 ]. Nevertheless, IVRA has some disadvantages including anesthetic toxicity, slow-onset, poor muscle relaxation, tourniquet pain, and minimal postoperative pain relief [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Intravenous regional anesthesia (IVRA) is mainly used in surgical operations with predicted durations of <1 h. Although this technique is useful for fractures of the upper extremity, especially distal to the elbow, and relieves the need for general anesthesia, it is limited by pain resulting from the application of tourniquets and postoperative pain ( 1 – 3 ). Increasing the efficacy of pain control in IVRA has been attempted by several authors, who have studied the addition of drugs, such as dexmedetomidine, dexamethasone, ketorolac and melatonin, to lidocaine in IVRA protocols, and reported enhanced anesthesia time and reduced pain perceived by patients ( 4 – 7 ).…”
mentioning
confidence: 99%